Fostering Awareness of Nationalism Through Pancasila Among High School Students - soesi idayanti; Moh Taufik (Universitas Pancasakti Tegal, 2021)
Youth and young people can play a bigger role in guarding the national development path. Various problems that arise as a result of a fading sense of nationalism and nationality have occurred recently, many young people or young people have experienced disorientation, dislocation and are involved in an interest that only cares for themselves or a certain group on behalf of the people as reasons for their activities. As the basis of the state, Pancasila must be a reference for the state in facing various global challenges in the developing world. The purpose of this study was to determine how the role of Pancasila in fostering a sense of nationalism and patriotism among high school students in Tegal Regency and to find out how the role of the government in fostering a sense of nationalism among high school students today Type of research is the literature. This research including library research because the data used is mostly secondary data in the form of documents related to Pancasila. The approach used in this research is philosophical. Fostering a sense of nationalism for high school students through Pancasila can be done from an early age, so that gradually with age it is hoped that a sense of nationalism will persist in the Indonesian nation. It can be started from the closest group, for example, family, because it is from the family that a sense of love for the country can be trained from an early age. Towards the younger generation, the State must be present as stipulated in the Preamble of the 1945 Constitution, the state protects all Indonesia's blood, including the young generation, high school children, where they are the young people of the nation who must be cared for and protected carefully.